CK2 kinase-mediated PHF8 phosphorylation controls TopBP1 stability to regulate DNA replication. Issue 19 (3rd October 2020) - Feng, Haihua; Lu, Jingchen; Song, Xiaotian; Thongkum, Angkana; Zhang, Fan; Lou, Lihong; Reizes, Ofer; Almasan, Alexandru; Gong, Zihua
Abstract: ATR functions as a master regulator of the DNA-damage response. ATR activation requires the ATR activator, topoisomerase IIβ-binding protein 1 (TopBP1). However, the underlying mechanism of TopBP1 regulation and how its regulation affects DNA replication remain unknown. Here, we report a specific interaction between TopBP1 and the histone demethylase PHF8. The TopBP1/PHF8 interaction is mediated by the BRCT 7+8 domain of TopBP1 and phosphorylation of PHF8 at Ser854. This interaction is cell-cycle regulated and phosphorylation-dependent. PHF8 is phosphorylated by CK2, which regulates binding of PHF8 to TopBP1. Importantly, PHF8 regulates TopBP1 protein level by preventing its ubiquitination and degradation mediated by the E3 ligase UBR5. Interestingly, PHF8pS854 is likely to contribute to regulation of TopBP1 stability and DNA replication checkpoint. Further, both TopBP1 and PHF8 are required for efficient replication fork restart. Together, these data identify PHF8 as a TopBP1-binding protein and provide mechanistic insight into how PHF8 regulates TopBP1 stability to maintain DNA replication.